2011
DOI: 10.1111/j.1467-7687.2011.01066.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro-analysis of infant looking in a naturalistic social setting: insights from biologically based models of attention

Abstract: A current theory of attention posits that several micro-indices of attentional vigilance are dependent on activation of the locus coeruleus, a brainstem nucleus that regulates cortical norepinephrine activity (Aston-Jones et al., 1999). This theory may account for many findings in the infant literature, while highlighting important new areas for research and theory on infant attention. We examined the visual behaviors of n = 16 infants (6-7 months) while they attended to multiple spatially distributed targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…Consistent with this, Geva et al (1999) found that in low arousal states after feeding, infants showed a novelty preference, whereas before feeding, in high arousal states, they showed a familiarity preference, thought to indicate that the infant had not yet habituated to the original stimulus. Similarly, in a paradigm with 6-7 month old infants, de Barbaro Chiba & Deák (2011) found that infants who showed faster responses to brightly-colored videos were more distracted by peripheral stimuli and showed more perseveration to the videos stimuli over the course of multiple trials, also suggesting a lack of habituation. While they did not measure or manipulate arousal levels, their measures of responsiveness were based on measures shown in monkeys to correspond with a continuum of brainstem arousal activity (Aston-Jones, Rajkowski, & Cohen, 1999).…”
Section: Running Head: Stress Reactivity and Attention In Infantsmentioning
confidence: 88%
“…Consistent with this, Geva et al (1999) found that in low arousal states after feeding, infants showed a novelty preference, whereas before feeding, in high arousal states, they showed a familiarity preference, thought to indicate that the infant had not yet habituated to the original stimulus. Similarly, in a paradigm with 6-7 month old infants, de Barbaro Chiba & Deák (2011) found that infants who showed faster responses to brightly-colored videos were more distracted by peripheral stimuli and showed more perseveration to the videos stimuli over the course of multiple trials, also suggesting a lack of habituation. While they did not measure or manipulate arousal levels, their measures of responsiveness were based on measures shown in monkeys to correspond with a continuum of brainstem arousal activity (Aston-Jones, Rajkowski, & Cohen, 1999).…”
Section: Running Head: Stress Reactivity and Attention In Infantsmentioning
confidence: 88%
“…Or are they observed because these experimental assessments tap some underlying “pure” aspect of cognition that is independent of naturalistic orienting? This question, which is relatively under-addressed in the literature (although see Aslin, 2009; de Barbaro, Chiba, & Deak, 2011; Hunnius, 2007; Rose, Feldman, & Jankowski, 2011b; Smith & Sheya, 2012), is the focus of the present article.…”
Section: Introductionmentioning
confidence: 96%
“…For example, research has suggested that adults with autism spectrum disorders (ASD) show reduced modulation of fixation duration by the semantic content at the point fixated (congruous versus incongruous) (Benson, Castelhano, Au-Yeung, & Rayner, 2012; see also Benson, Piper, & Fletcher-Watson, 2009; Kemner, Verbaten, Cuperus, Camfferman, & van Engeland, 1998; Landry & Bryson, 2004). “Inflexible” orienting styles, in which saccades are relatively more driven by internally generated saccade timing mechanisms, have been contrasted with “flexible” orienting styles in which process monitoring and the viewer's interest in the point fixated play a relatively greater role in determining fixation duration (Henderson & Smith, 2009; Nuthmann et al, 2010; see also Aston-Jones, Rajkowski, & Cohen, 1999; de Barbaro et al, 2011). This suggests the importance of studying variance in fixation duration as a parameter of individual differences independent of mean fixation duration.…”
Section: Introductionmentioning
confidence: 99%
“…We previously tested some of the behavioral predictions of the AJMA in a rich naturalistic environment with many potential distractors (de Barbaro, Chiba, & Deák, 2011). We assessed 6-7 month old infants' responsivity to peripherally located videos via a number of features previously used to classify infants as "fast" or "slow" lookers, including duration of fixations, reorientation speed, and time spent looking at video stimuli.…”
Section: Introductionmentioning
confidence: 99%